Penerapan Budaya Organisasi dalam Peningkatan Pelayanan Administrasi Pendidikan di MAN 2 Bone - Ananda Musli, Firdiana; Arsyad, Arisal (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
This thesis discusses the Application of Organizational Culture in Improving Administrative Services at MAN 2 Bone. The purpose of this study is to find out the extent of the application of organizational culture in improving the educational administration process. The type of research used in this study is qualitative research. This research uses a management approach and a sociological approach. In collecting data, observation, interview, and documentation methods are used. As well as using data analysis techniques, namely data reduction, data presentation and conclusion drawn. The results of this study show that there is indeed an organizational culture policy in MAN 2 Bone that has existed for a long time, one of the cultures that is upheld in MAN 2 Bone is the culture of "sipakatau, sipakainge, sipakalebbi" which means "mutual respect, mutual respect and mutual reminding" along with other cultures that are also in the form of rules and regulations in the madrasah. This organizational culture is expected to be able to be a reference for all madrasah stakeholders in carrying out their obligations, be it as students, teachers, employees or principals. However, so far there are still some employees who do not implement the existing organizational culture well, such as in administrative services at MAN 2 Bone which are still felt to be lacking, especially in service to guests, even though by implementing the organizational culture well, it will make the image and reputation of the madrasah even better in the eyes of school residents and the community outside the madrasah. The implementation of organizational culture is needed in all fields, be it students, teachers or employees.